Perceived coaches’ health promotion activity, maintenance of participation in sports, and lifestyle habits among emerging adults: a four-year follow-up study - Rinta-Antila, Katja; Koski, Pasi; Aira, Tuula; Heinonen, Olli J.; Korpelainen, Raija; Parkkari, Jari; Savonen, Kai; Toivo, Kerttu; Uusitalo, Arja; Valtonen, Maarit; Vasankari, Tommi; Villberg, Jari; et al. (Annals of medicine (Helsinki), 2024)
This study focused on how adolescents' perceptions of coaches' health promotion activity predict maintained participation and dropout in organized sports in emerging adulthood. In addition, differences in lifestyle habits between maintainers, dropouts, and nonparticipants in organized sports were explored. Overall, 616 adolescents reported organized sports participation in the Finnish Health Promoting Sports Club (FHPSC) study at ages 15 and 19. Of these, 323 reported coach's health promotion activity on health topics at the age of 15. An index of a coach's general health promotion activity was formed. At age 19, all study participants reported their lifestyle habits. Among males, those who had perceived coaches' general health promotion activity as frequent were more likely to be maintainers than dropouts (48.6% vs. 20.0%) ( = .002). Among females, there was no significant difference (32.0% vs. 28.4%). Logistic regression analysis adjusted for gender showed that perceiving coach's general health promotion activity as frequent increased the odds of being a maintainer rather than a dropout. Moreover, maintainers had higher odds of having healthy lifestyle habits when compared to nonparticipants (related to physical activity; sleep; fruit and vegetable consumption; and cigarette use) or dropouts (related to physical activity; and cigarette use). In addition, dropouts had higher odds of having healthy lifestyle habits than nonparticipants (related to sleep; and cigarette use). Perceiving coaches' health promotion activity as frequent was related to maintained participation in organized sports among males. Maintainers were more likely to have more healthy lifestyle habits than nonparticipants and dropouts. There is a need to invest in coaches' health promotion activity when it is infrequent. A more detailed understanding is needed of coaches' health promotion activity that supports both maintained participation in sports, especially among females, and healthy lifestyle habits in emerging adulthood.